Studying ICD-11 Primary Health Care bodily stress syndrome in Brazil: do many functional disorders represent just one syndrome? - Fortes,Sandra (2019)
Objective: Disorders characterized by “distressing unexplained somatic symptoms” are challenging. In the ICD-11 Primary Health Care (PHC) Guidelines for Diagnosis and Management of Mental Disorders (ICD-11 PHC), a new category, bodily stress syndrome (BSS), was included to diagnose patients presenting unexplained somatic symptoms. The present study investigated the association of BSS with anxiety, depression, and four subgroups of physical symptoms in a Brazilian primary health care (PHC) sample. Methodology: As part of the international ICD-11 PHC study, 338 patients were evaluated by their primary care physicians, followed by testing with Clinical Interview Schedule (CIS-R) and World Health Organization Disability Assessment Schedule, Version 2.0 (WHODAS 2.0). BSS was diagnosed in the presence of at least three somatic symptoms associated with incapacity. The association between anxiety, depression, and four subgroups of physical symptoms with being a BSS case was analyzed. Results: The number of somatic symptoms was high in the overall sample of 338 patients (mean = 8.4), but even higher in the 131 BSS patients (10.2; p < 0.001). Most BSS patients (57.3%) had at least three symptoms from two, three, or four subgroups, and these were associated with anxiety and depression in 80.9% of these patients. The symptom subgroup most strongly associated with “being a BSS” case was the non-specific group (OR = 6.51; 95%CI 1.65-24.34), followed by musculoskeletal (OR = 2,31; 95%CI 1.19-4.72). Conclusion: Somatic symptoms were frequent in a sample of PHC patients in Brazil. In the present sample, one third were BSS cases and met the criteria for at least two symptom subgroups, supporting the hypothesis that different functional symptoms are related to each other.